SHORT FILM MEDIA UTILIZATION IN CIVIC EDUCATION LEARNING PROCESS IN DEVELOPINGSTUDENTS CREATIVITY - Kokom Komalasari3, Silvan Egistian N Aim Abdulkarim (Jurnal Civicus, 2016)
This study started from the researcher distress to the problem that occurs in class VIII-A SMPN 14 Bandung associated with the development of the creativity of the learners in learning Civic Education. This could be seen from the learning process centered on the educators or teacher centered and the learners were not accustomed to develop ideas in which later it poured into a product of learning. The method which was used was the method of classroom action research (PTK) with through the stages of plan, implementation, observation, analysis and reflection on classes VIII-A SMPN 14 Bandung. The data collection techniques which were used were observation, interview, field note, documentation study, and questionnaires. Based on the results of the action research, the use of short film media as a medium of Civic Education learning process had succeeded in developing the creativity of the learners. This improvement could be seen from the results of the implementation of the research conducted during three cycles, the students were able to make and featured short films creatively in accordance with the materials in the Civic Education learning process. The improvementwas seen in the characteristics or creativity indicators of the learners which were grown. Thus, short film media utilization as a Civic Education learning media can develop the creativity of learners.Keywords: Media Short Film, Student Creativity